PENGARUH LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PADA UMKM - Tri Wulandari (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This research uses quantitative methods with descriptive research types. with 48 respondents. The data analysis technique used is descriptive analysis and simple linear regression analysis. Based on the results of the study, financial literacy affects financial management by 30.4%, while 69.6% is influenced by other factors not examined in this study. financial literacy in UMKM of assisted members of Pematang Johar Village, Labuhan Deli District is in the low category, this needs to increase knowledge about finance in order to help UMKM in managing finances. The low financial literacy of UMKM in this study is influenced by several things, namely the level of education, receipt of information about finance, and the age of UMKM actors.